(untitled) - United nations conference on trade and development (Switzerland, 2010)
UNCTAD’s Technology and Innovation Report 2010 focuses on the technological challenges that small-holder farmers in developing countries, especially sub-Saharan Africa, face in increasing agricultural productivity. It outlines the agricultural sector’s challenges and the roles of technology and innovation in rising production and the income of small-holder farmers. And it describes readily available technologies that can be applied now to improve soils, manage water shortages and resist drought.
Keywords: Sự đổi mới nông nghiệp,An toàn thực phẩm,Agricultural innovations,Sub-Saharan,Food security; Africa,Periodicals,Africa